2017
DOI: 10.1155/2017/8574184
|View full text |Cite
|
Sign up to set email alerts
|

Increased Melting Heat Transfer in the Latent Heat Energy Storage from the Tube-and-Shell Model to the Combine-and-Shell Model

Abstract: The melting of paraffin in thermal storage tube-and-shell and combine-and-shell models was conducted with the numerical research aim of decreasing the charge time through changing the shape of the tube into combining form. The results discussed are temperature contour, liquid-solid interface contour, temperature distribution, liquid fraction, and the average Nusselt number. The results show that the charge time in the tube-and-shell model is 2000 s, while the combine-and-shell model is 1200 s, meaning an overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…As the present study is carried out fully computational, initially the grid and validation along with time dependency were studied with the experimentally and numerically observed transient data by the Korawan et al [34] The simulated results show good agreement with the reported earlier data published as shown in Figure 3. Thus, a similar concept of the boundary was adopted in the present simulation.…”
Section: Battery Assembly and Fluent Modelssupporting
confidence: 78%
See 3 more Smart Citations
“…As the present study is carried out fully computational, initially the grid and validation along with time dependency were studied with the experimentally and numerically observed transient data by the Korawan et al [34] The simulated results show good agreement with the reported earlier data published as shown in Figure 3. Thus, a similar concept of the boundary was adopted in the present simulation.…”
Section: Battery Assembly and Fluent Modelssupporting
confidence: 78%
“…For the purpose of numerical validation, a set of thermal properties of paraffin was taken from the Korawan et al [34] The initialized boundary condition of the models is presented in Table 3.…”
Section: Battery Assembly and Fluent Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is also another way to accelerate the time of melting without adding a surface area of the hot wall, that is by changing the shape of the model of tube-and-shell into a nozzle-andshell [10], the results show that melting time in the nozzle-and-shell model is 15.3% faster than the tube-and-shell model. Other research was carried out by changing the shape of the tubeand-shell into combine-and-shell [11]. The result showed that the melting time in the combineand-shell model was 40% faster than the tube-and-shell model.…”
Section: Introductionmentioning
confidence: 99%